(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
The study was conducted to advance points in relations to the effects of multimedia technology usage during the 2023 elections in Nigeria. The researchers relied on secondary data sources to advance a discourse of the subject of the effect of multimedia usage in the 2023 elections in Nigeria. Anchored on the social responsibility theory, the study encouraged media practitioners to produced multimedia contents that perform the roles the society entrusts on a journalist. The effect of multimedia usage during the 2023 elections was seen in election jingles, advertorials, campaign messages, posters, pictorials and how live and recorded reports from various polling units across the country were covered and reported simultaneously. Multimedia gave Nigerians a real time effect of the happenings. The usage of multimedia in the 2023 general elections in Nigeria was multidimensional and it affected every aspect of the electoral process ranging from civic engagement to disseminating effective electoral messages, increase in youth participation and keenly monitoring the election processes. However, malfunctioning of multimedia technologies and the use of multimedia platforms to spread misinformation, disinformation, fake news, hate speech were among the challenges.